Sildenafil for idiopathic pulmonary fibrosis: A systematic review and meta-analysis. (June 2022) - Pitre, Tyler; Khalid, Muhammad Faran; Cui, Sonya; Zhang, Melanie C.; Husnudinov, Renata; Mah, Jasmine; Helmczi, Wryan; Su, Johnny; Guy, Brent; Scallan, Ciaran; Jones, Aaron; Zeraatkar, Dena
Abstract: Background: Patients with idiopathic pulmonary fibrosis have a poor overall prognosis and there are few evidence-based drug therapies that reduce mortality. Objective: We aimed to perform a systematic review and meta-analysis to assess whether sildenafil reduces mortality, disease progression and adverse side effects. Methods: We reviewed randomized controlled studies (RCTs) from MEDLINE, Cochrane registry of clinical trials, and EMBASE. Our outcomes of interest included mortality, change in FVC, acute exacerbations and hospitalizations and adverse drug effects leading to discontinuation. We used an inverse variance fixed effects meta-analysis method to calculate pooled relative risk (RR) and mean difference (MD). Results: A total of 4 studies were included in the systematic review. Sildenafil probably reduces mortality when compared to placebo or to standard care, [RR 0.73 (95% CI 0.51 to 1.04); moderate certainty]. Pooled estimates showed sildenafil may not alter the rate of change of FVC [MD 0.61% (95% CI -0.29 to 1.52)], or DLCO [MD 0.97% (95% CI 0.04 to 1.90)] (both low certainty). Pooled estimated showed sildenafil may not reduce the number of hospitalizations or acute exacerbations, [RR 1.10 (95% CI 0.61 to 1.98); low certainty]. There is probably no difference in drug discontinuation due to adverse effects when comparing sildenafil to the control group, [RR 0.79 (95% CI 0.56, 1.10); moderate certainty]. Conclusion: Sildenafil probably reduces all-cause mortality in IPF patients. More studies need to be done to confirm the magnitude and reliability of the point estimate.